Two new species of Billolivia (Gesneriaceae) from the Langbiang Plateau, Vietnam - Trường, Lưu Hồng; Nhân, Phạm Hữu; Đạt, Nguyễn Quốc; Văn, Nguyễn Thế; Mến, Nguyễn Thành; Long, Vũ Ngọc (Phytotaxa, 2018)
Two new species of the recently established genus Billolivia (Gesneriaceae) are described from the Langbiang Plateau in the Central Highlands of Vietnam, namely B. noanii and B. trucii. Their conservation status is assessed. These findings increase the total number of Billolivia species to be 13. A key to all known species of the genus is given.